Group C Neisseria meningitidis as a Cause of Septic Arthritis in a Native Shoulder Joint: A Case Report - Amy J. Garner; Freda Sundram; Kathryn Harris (Case Reports in Orthopedics)
Septic arthritis is an Orthopaedic emergency, threatening the joint within hours of onset. Up to 10% of cases of meningococcaemia have an associated septic arthritis. The aetiology of acute meningococcaemia in a variety of clinical syndromes is well documented in the literature. The pathogen Neisseria meningitidis can cause both primary and secondary manifestations of disseminated infection. Broad-range 16S rDNA PCR is a relatively new technique, useful in identifying aetiological agents in septic patients with negative blood cultures. Here, we describe the rare clinical scenario of a 76-year-old woman with primary meningococcal septic arthritis of a native shoulder joint without associated meningococcal bloodstream infection. We discuss the role of 16s rDNA Polymerase Chain Reaction (PCR) in the identification of the infectious agent, Neisseria meningitidis, and the role of this technique in guiding subsequent management.